"Acting head of the household" of Chinese left-behind families: A neglected phenomenon. (March 2021) - Li, Wentian
"Acting head of the household" is a psychological phenomenon of the left-behind families in China. It was named by the author. That is, a left-behind woman with maladaptation and difficulties in role change usually actively establish a very close connection with a role outside the family after the husband's departure from home. In the process of helping and supporting the left-behind family, the role becomes the actual decision-maker, instructor, and even savior of the family, and eventually instead becomes the actual "head of the household" of the family. The left-behind family's "acting head of the household" is a unique phenomenon in the development of Chinese society under its culture. This phenomenon has not yet attracted widespread attention and is a blind spot in Chinese mental health and psychosocial services.